Legal Safeguards Against Mob Justice: An Analysis of Blasphemy Laws in Pakistan and International Human Rights Norms (Al-Qamar, 2023)
This research article aims to analyze the legal guarantees against mob justice, specifically in relation to blasphemy laws in Pakistan and international human rights standards. The study utilizes a qualitative research methodology by examining the constitutional guarantees against mob justice in Pakistan and the international human rights laws that prohibit vigilante actions. The Universal Declaration of Human Rights (1948) and the International Covenant on Civil and Political Rights (1966) are analyzed to understand the legal framework that prohibits mob justice and affirms individuals' rights to a fair trial. The study emphasizes the need to protect vulnerable groups, such as religious minorities, and examines how international human rights law can be used to combat mob justice. The research concludes that while Pakistan has a legal framework to prevent mob justice, gaps and challenges remain in implementing these laws. Therefore, greater awareness of legal rights and protections against mob violence and upholding the rule of law is needed to promote respect for human rights. The study suggests enforcing and upholding legal safeguards against mob justice to protect individuals' rights and combat mob violence in Pakistan.
Keywords: Mob Justice; Blasphemy Laws; Life Safeguards; International Human Rights; Norms